Optimalisasi Durasi dan Biaya Proyek Bendungan Cibeet Paket 1 Menggunakan Metode Least Cost Analysis dengan Penambahan Tenaga Kerja dan Jam Lembur - Edi Purnomo; rachmat mudiyono; kartono wibowo (UNISSULA Semarang, 2025)
This study aims to optimize project duration and minimize additional costs in the Cibeet Dam Package 1 project by applying the Least Cost Analysis method through strategies of increasing labor workforce and adding overtime hours (1, 2, and 3 hours). Primary and secondary data were collected from project documents and analyzed using Microsoft Project to identify the critical path and perform crashing simulations, as well as Microsoft Excel for cost calculations. The results indicate that increasing labor can accelerate the project duration by up to 15.8% with a 12% increase in cost, while adding overtime hours provides acceleration with relatively lower additional costs. The combination of both strategies yields an optimal balance, achieving a 22.7% reduction in duration with a 15.8% cost increase. This study reinforces the effectiveness of the Least Cost Analysis method as a strategic tool in project management decision-making, especially for controlling risks of delays and cost overruns in construction projects. Further research is recommended to include external variables for more comprehensive outcomes